Growth and Maintenance of Escherichia coli Laboratory Strains. Issue 1 (20th January 2021) - Tuttle, Amie R.; Trahan, Nicholas D.; Son, Mike S.
Abstract: Escherichia coli is a Gram‐negative bacterium, commonly used in both teaching and research laboratories. This article includes protocols for the growth and maintenance of E. coli in any teaching‐ or research‐associated laboratory. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Growth of E. coli from frozen stocks Basic Protocol 2 : Growth of E. coli in liquid media Basic Protocol 3 : Enumeration of E. coli on solid media Basic Protocol 4 : Storage of E. coli frozen stocks in glycerol Basic Protocol 5 : Storage of E. coli in agar stabs Basic Protocol 6 : Growth curve of E. coli liquid culture